(untitled) (Revista Iberoamericana de Bioética, 2017)
Advances in the area of reproduction constantly raise important bioethical questions and, occasionally, legal ones. Thus, ever more precise predictive genetic diagnoses force us to take decisions such as whether or not to have a child with a disability or proceed with abortion, etc. In this research paper, the ethical aspects in conflict are analyzed, taking into account the legal regulation in place in relation to these increasingly common practices.